Lack of host phylogenetic structure in the gut bacterial communities of New Zealand cicadas and their interspecific hybrids - Diler Haji; Jason Vailionis; Mark Stukel; Eric Gordon; Emily Moriarty Lemmon; Alan R. Lemmon; Chris Simon (Scientific Reports, 2022)
Abstract Host-microbe interactions are intimately linked to eukaryotic evolution, particularly in sap-sucking insects that often rely on obligate microbial symbionts for nutrient provisioning. Cicadas (Cicadidae: Auchenorrhyncha) specialize on xylem fluid and derive many essential amino acids and vitamins from intracellular bacteria or fungi (Hodgkinia, Sulcia, and Ophiocordyceps) that are propagated via transmission from mothers to offspring. Despite the beneficial role of these non-gut symbionts in nutrient provisioning, the role of beneficial microbiota within the gut remains unclear. Here, we investigate the relative abundance and impact of host phylogeny and ecology on gut microbial diversity in cicadas using 16S ribosomal RNA gene amplicon sequencing data from 197 wild-collected cicadas and new mitochondrial genomes across 38 New Zealand cicada species, including natural hybrids between one pair of two species. We find low abundance and a lack of phylogenetic structure and hybrid effects but a significant role of elevation in explaining variation in gut microbiota.